The occurrence of air masses and atmospheric fronts in the Mrocza community area - Więcław, Mirosław (Journal of Education, Health and Sport, 2017)
The aim of the paper was to investigate the annual and long-term variability of frequency of air masses and atmospheric fronts in the Mrocza community area. The synoptic maps from 00 UTC were the basis for the designation of air masses and atmospheric fronts observed over the area of research. The analysis was carried out on the basis of the data collected from 1996 to 2010.